Enamel matrix derivative effects on palatal mucosa wound healing: Randomized clinical trial - Miguel, Manuela Maria Viana [UNESP]; Mathias-Santamaria, Ingrid Fernandes [UNESP]; Rossato, Amanda [UNESP]; Ferraz, Laís Fernanda Ferreira [UNESP]; Rangel, Thiago Perez; Casarin, Renato Corrêa Viana; Tatakis, Dimitris N.; Santamaria, Mauro Pedrine [UNESP] (Wiley, 2021)
Background: This study was conducted to evaluate the clinical, immunologic, and patient-centered outcomes of enamel matrix protein derivative (EMD) on excisional wounds in palatal mucosa. Materials: Forty-four patients in need of ridge preservation were randomly allocated into two groups: control group (n = 22): open palatal wound after free gingival graft (FGG) harvest and EMD group (n = 22): open palatal wound after FGG harvest that received 0.3 ml of EMD. Clinical and patient-centered parameters were analyzed for 3 months post-treatment. Wound fluid levels of inflammatory markers were assessed 3 and 7 days postoperatively. Results: No significant inter-group difference was observed in remaining wound area and re-epithelialization. EMD and control groups achieved wound closure and re-epithelialization 30 days postoperatively (p <.001), without inter-group differences. Similarly, number of analgesics and Oral Health Impact Profile scores did not present significant inter-group differences (p >.05). EMD appeared to selectively modulate wound fluid levels of monocyte chemoattractant protein-1, macrophage inflammatory protein-1α, matrix metallopeptidase 9, and tissue inhibitor of metalloproteinases-2. Conclusion: Within the limits of the present study, it can be concluded that EMD application to excisional palatal wounds using the investigated protocol does not provide clinical healing benefits, despite an apparent modulation of selected inflammatory markers.
Keywords: enamel matrix proteins; gingival recession; palate; patient outcome assessment; wound healing